2020
DOI: 10.1002/cctc.201902371
|View full text |Cite
|
Sign up to set email alerts
|

Advanced X‐ray Absorption Spectroscopy Analysis to Determine Structure‐Activity Relationships for Cu‐Zeolites in the Direct Conversion of Methane to Methanol

Abstract: An industrial process for direct conversion of methane to methanol (DMTM) would revolutionize methane as feedstock for the chemical industry and it would be a cherished contribution to climate change mitigation. At the present stage, it is a rather remote perspective, but the search for the materials that would make it possible and economically viable, is very active. Cu‐exchanged zeolites have been shown to cleave the C−H bond of methane at low temperatures (≤200 °C), and has been extensively studied for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 171 publications
(262 reference statements)
1
30
0
Order By: Relevance
“…No signals due to any Cu III species were detected [64] . The small shoulder at 8983 eV is due to the 1s→4p transitions in Cu I species, [19, 30, 33, 61–63] formed via autoreduction, as was also observed in FTIR experiments. Upon the reaction with methane, the intensity of this signal significantly increases due to the increasing fraction of Cu I .…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…No signals due to any Cu III species were detected [64] . The small shoulder at 8983 eV is due to the 1s→4p transitions in Cu I species, [19, 30, 33, 61–63] formed via autoreduction, as was also observed in FTIR experiments. Upon the reaction with methane, the intensity of this signal significantly increases due to the increasing fraction of Cu I .…”
Section: Resultssupporting
confidence: 69%
“…Activation in oxygen and reaction with methane induce the change of copper oxidation state and local environment, which was analyzed by X‐ray absorption spectroscopy (Figure 1 B). In the spectra of oxygen‐activated samples, two main signals at 8977 and 8986 eV are present, corresponding to dipole forbidden 1s→3d and 1s→4p transitions in tetra‐coordinated Cu II species, respectively [19, 30, 33, 61–63] . These peaks appear in the copper‐exchanged zeolites after the high‐temperature activation, indicating the transformation of hydrated octahedral Cu(H 2 O) 6− x (OH) x (2− x )+ to the extra‐framework copper species bond to the ion‐exchange positions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, significant progress in the design and engineering of novel copper‐containing materials for the direct conversion of methane to methanol was achieved [28–31] . It was reported that copper hosted in zeolites of different topology (MFI, [16, 17] MOR, [18, 19] CHA, [24, 32] FAU, [33] FER, [34] ERI, [35] and MAZ [36] ), and supported on alumina or silica [37, 38] can activate methane.…”
Section: Introductionmentioning
confidence: 99%
“…In general, XAS measurement exhibits the following advantages: 176 temporal resolutions for an in-situ experiment. Hence, XAS has been extensively utilized in the study of material science in recent years, 182,183 especially in the research of some element-doped materials, such as Cu-exchanged zeolites, 184 P-doped hematite, 185 Ta-doped α-Fe 2 O 3 nanorods, 186 and P-B co-doped amorphous porous NiFe-based material. 187 Therefore, the future looks bright for the use…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 99%